A Web-based System to Assist With Etiology Differential Diagnosis in Children With Arterial Ischemic Stroke. Issue 5 (October 2021) - Karthik, Anjini; Jiang, Bin; Li, Ying; Hills, Nancy K.; Kuchherzki, Maria; deVeber, Gabrielle A.; Barkovich, A. James; Fullerton, Heather J.; Wintermark, Max
Abstract: Background and Purpose: The diagnosis of childhood arteriopathy is complex. We present a Web-based, evidence-backed classification system to return the most likely cause(s) of a pediatric arterial ischemic stroke. This tool incorporates a decision-making algorithm that considers a patient's clinical and imaging features before returning a differential diagnosis, including the likelihood of various arteriopathy subtypes. Methods: The Vascular Effects of Infection in Pediatric Stroke study prospectively enrolled 355 children with arterial ischemic stroke (2010–2014). Previously, a central panel of experts classified the stroke etiology. To create this tool, we used the 174 patients with definite arteriopathy and spontaneous cardioembolic stroke as the "derivation cohort" and the 34 with "possible" arteriopathy as the "test cohort." Using logistic regression models of clinical and imaging characteristics associated with each arteriopathy subtype in the derivation cohort, we built a decision framework that we integrated into a Web interface specifically designed to create a probabilistic differential diagnosis. We applied the Web-based tool to the "test cohort." Results: The differential diagnosis returned by our tool was in complete agreement with the experts' opinions in 20.6% of patients. We observed a partial agreement in 41.2% of patients and an overlap in 29.4% of patients. The tool disagreed with the experts on the diagnoses of 3 patients (8.8%). Conclusions: Our tool yielded an overlapping differential diagnosis in most patients that defied definitive classification by experts. Although it needs to be validated in an independent cohort, it helps facilitate high-quality, and timely diagnoses of arteriopathy in pediatric patients. Abstract : Supplemental Digital Content is available in the text